Fā’ālīyātu āl-Wāsīlāh āt-Tā'līmīyyāh "Fīīdīyū āl-Mutāḥārrīkāh āl-Mu'tāmīdāh 'Alā Anīmāker" līī-Tārqīyātī Nātīījātī Tā'līmī ās-Shārf līī-Ṭhālībātī āl-Fāṣlī āth-Thsānī bīī-Mā'hādī Dārīssālām Gontor - Abdul Hafidz Bin Zaid; Safira Aina Najiyah; Ifa Rodifah Nur; Fadhilah Fatimatuzzahra; Nabila Qanita (Mantiqu Tayr: Journal of Arabic Language, 2025)
Sharf is a crucial branch of Arabic grammar, essential for understanding the structure, forms, and changes of words in Arabic language. Therefore, mastering Sharf required accurate and comprehensive understanding. However, some 2nd grade students find Sharf to be a difficult subject which can negatively impact their learning outcomes. Hence, there is a need for effective learning media that can enhance students’ understanding of Sharf. This study aims to determine the effectiveness of Animaker-based animated media in improving Sharf learning outcomes of 2nd-grade students at KMI in Gontor Putri 1. This research employs a quantitative method with an experimental approach, utilizing a True Experiment design in the form of a Post-Test Only Control Group. The research subjects were 42 students in the 2nd grade at KMI Gontor Putri 1. The data collection techniques used were interviews, tests, and documentation. The data analysis technique in this research involved descriptive analysis, prerequisite tests, and differences tests using the U-test (Mann-Whitney). The collected data was then analyzed using SPSS software. The findings indicate that Animaker media effectively improves learning outcomes in the Sharf subject. This is evidenced by a significance value (2-tailed sig) of 0.004 from the Mann-Whitney U-test, which is less than 0.05. Thus, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. These, results confirm that Animaker animated media significantly enhances students’ understanding of Sharf. This study contributes to Arabic language studies by introducing an innovative and engaging learning medium that enhances students understanding of Sharf. This research contributes to Arabic language education by introducing an innovative and engaging learning medium tailored to modern educational needs. Future studies could expand the application of Animaker-based animated media to other branches of Arabic studies, evaluate its long-term impact on learning outcomes, and explore its effectiveness in diverse educational settings. Researchers might also investigate the integration of such media with other technological tools to create a more comprehensive learning experience.